The application of ACOTEC system in the industrialised building system: the case study of medium cost apartment in Sungai Nibong, Pulau Pinang / Ahmad Mu’az Ahmad - Ahmad, Ahmad Mu’az (2017)
Industry of construction has been revolved from many centuries. As we known the traditional method of construction has many disadvantages than advantages. Within the past the engineer has been develop new technology to clear the disadvantages that been faced by many contractors. The technology is called as Industrialised Building System(IBS) that a technology that give the east to do work. Also the IBS has effect the cost of construction and duration of construction. This report will enlighten readers about the Industrialised Building System(IBS) that been applicate to the construction of Medium Cost Apartment. To gain the information about this title report, the writer did an observation by himself at the site and also referred to books from the USM library and writer also did a few interviews with the site personnel. The tittle of this report is “The Application of ACOTEC System in the Industrialised Building System (IBS): The case Study of Medium Cost Apartment in Sungai Nibong” as a case study.